1953
DOI: 10.1029/tr034i004p00539
|View full text |Cite
|
Sign up to set email alerts
|

The radioactivity of bottom sediments in Chesapeake Bay

Abstract: Very little is known of the natural radioactivity exhibited by continental‐shell sediments off the eastern coast of the United States. A knowledge of the level of this activity is most important if future surveys are to utilize radiometric techniques for the solution of oceanographic problems. Activities were determined for a group of samples from selected locations in the Chesapeake Bay area. The apparatus for making these measurements is described. Results are used to show the distribution of natural radioac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1961
1961
2003
2003

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…A clear relation was shown by Jaffe and Hughes Beach sand from Florida _________________ _ (1953) between the radioactivity and the grain size of Beach sand from Galveston Island, Tex ___ _ sediment in samples from the bottom of the Chesapeake Five samples of sandstone analyzed by Adams and Weaver (1958, p. 399) Probably the average sandstone has between 2 and 24 ppm of Th, the average possibly being 5.4 ppm (Rankama and Sahama, 1950, p. 573;Adams and Weaver, 1958, p. 402, 413;Murray and Adams, 1958, p. 265). Results of work by Jaffe and Hughes (1953), Breger (1955, p. 63), and Murray and Adams (1958, p. 263) suggested that in ordinary sedimentary sequences the amount of thorium is less in sandstone than in shale.…”
Section: Average Shale (Estimate) _____________________________ 12±1mentioning
confidence: 99%
See 1 more Smart Citation
“…A clear relation was shown by Jaffe and Hughes Beach sand from Florida _________________ _ (1953) between the radioactivity and the grain size of Beach sand from Galveston Island, Tex ___ _ sediment in samples from the bottom of the Chesapeake Five samples of sandstone analyzed by Adams and Weaver (1958, p. 399) Probably the average sandstone has between 2 and 24 ppm of Th, the average possibly being 5.4 ppm (Rankama and Sahama, 1950, p. 573;Adams and Weaver, 1958, p. 402, 413;Murray and Adams, 1958, p. 265). Results of work by Jaffe and Hughes (1953), Breger (1955, p. 63), and Murray and Adams (1958, p. 263) suggested that in ordinary sedimentary sequences the amount of thorium is less in sandstone than in shale.…”
Section: Average Shale (Estimate) _____________________________ 12±1mentioning
confidence: 99%
“…Very little of the thorium in common sand was said to be associated with heavy detrital minerals, and common sands contain only from one-twentieth to one-third as much thorium as shale. Offshore shales contain more thorium than nearshore sands and beach sediments (Jaffe and Hughes, 1953;Breger, 1955, p. 63;Adams and Weaver, 1958, p. 396--399, 412-413;Murray and Adams, 1958, p. 263, 267-268;Adams and others, 1958, p. 272). If the monazite in the metamorphic rocks is interpreted to be a metamorphic mineral formed from components available in the sediment and if the facies of metamorphism and concentration of components is interpreted to control the rate of nucleation of monazite during metamorphism, then the abundance of monazite should be greatest in those metamorphic rocks that initially had the most thorium :and other necessary components and were metamorphosed to the highest facies.…”
Section: -813-67-13mentioning
confidence: 99%
“…To the writer's knowledge, however, the amounts of uranium and other chemical constituents of the deposited black muds have been determined and the chemical regimen of the overlying waters is fairly well known for only two areas the fjords of southern Norway and the Baltic Sea (table 3). Some data on the Chesapeake Bay (Jaffe and Hughes, 1953), on the Atlantic Ocean ........................................................... Framvaren ________________________________ Drammensfjord .................................................... Koczy, Tomic, and Hecht (1957) i Str0m (1948). * Contains 3.2 cu cm oxygen per liter (Strtfm, 1948).…”
Section: Salinitymentioning
confidence: 99%
“…A possible explanation for the high gamma intensity in this area is that the depression may have formed an area of reduced wave effects and lower current speeds, resulting in greater accumulation of fine sediments in the depression relative to the rest of the area. Work conducted on the inner shelf of the western Atlantic showed that gamma intensity tends to increase with decreasing sediment particle size (Jaffe and Hughes, 1953; FERRY-SPATIAL AND TEMPORAL DISTRIBUTION OF DREDGED SEDIMENTS 19 Grosz and Escowitz, 1983;Grosz, 1987;Grosz et al, 1989;Grosz et al, 1990). An increase in fine-grained sediJnent accumulation in the depression would account for the relatively higher gamma intensities measured in that area.…”
Section: Discussionmentioning
confidence: 99%